Chapter 6-Miscellaneous Ordinances, Article 26-Concealed Weapons, §§ 483-486 in The Municipal Code of Berlin (1890). - (:unkn) unknown (My University, 1890)
It shall be unlawful for any person, within the limits of the City of Berlin, to carry or wear under his clothes, or concealed about his person, any pistol, colt or slung shot, cross knuckles, or knuckles of lead, brass or other metal or bowie knife, dirk knife or dirk, razor or dagger, or any other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED